EVALUASI AKTIVITAS TRANSAMINASE, DAN KADAR BILIRUBIN PADA PENDERITA VIRUS HEPATITIS B DAN C - Yosepin .; Benny Rusli; Hardjoeno . (Indonesian Association of Clinical Pathologist and Medical laboratory, 2009)
Hepatitis virus replicates only in hepatocyte. In hepatocyte injury, transaminase enzymes which normally intracellularly will transform to the blood circulation. And there are variation of increasing transaminase activities in HBV and HCV. To evaluatetransaminase activities, and bilirubin level in patients with HBV and HCV. Study design was cross sectional of 76 patients with HBVand HCV, data from medical record at Wahidin Sudirohusodo Hospital, Makassar, from January 2006 until July 2008 period. Datawas analyzed with Mann Whitney test using SPSS. windows versi on 12. of 76 patients with HBV and HCV were found 59 Men and 17women, age 15–72 years old. In there were no statistical significance between transaminase activites, bilirubin direct,indirect (p > 0.05),but there was significance difference of total bilirubin between HBV and HCV (p < 0.05). There were no statistical difference of AST,ALT, bilirubin direct and bilirubin indirect between HBV and HCV. Injury hepatocelluler because of HBV and HCV can not be identifiedjust by transaminase activities and bilirubin level, but there are other factor that influence.